2018
DOI: 10.1371/journal.pone.0197592
|View full text |Cite
|
Sign up to set email alerts
|

The influence of increased distal loading on metabolic cost, efficiency, and kinematics of roller ski skating

Abstract: The purpose of the present study was to examine the influence of increased loading of the roller ski on metabolic cost, gross efficiency, and kinematics of roller ski skating in steep and moderate terrain, while employing two incline-specific techniques. Ten nationally ranked male cross-country skiers were subjected to four 7-minute submaximal intervals, with 0, 0.5, 1.0, and 1.5 kg added beneath the roller-ski in a randomized order. This was done on two separate days, with the G2 skating at 12% incline and 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Furthermore, the manufacturer positioned the binding with the rotational hinge approximately 2.0 and 6.5 cm in front of the ski center of mass for the on-snow skis and roller skis, respectively. Bolger et al (2018) reported small adjustments of foot displacement with 0.5 kg added underneath each roller ski when skating on steep inclines using a different sub-technique ("V1", "Gear 2" or "paddling"). The same research group also reported small but significant changes in muscle coordinative patterns, but no changes in gross efficiency or cycle characteristics when they altered the antero-posterior position of the ski boot according to the rotational hinge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the manufacturer positioned the binding with the rotational hinge approximately 2.0 and 6.5 cm in front of the ski center of mass for the on-snow skis and roller skis, respectively. Bolger et al (2018) reported small adjustments of foot displacement with 0.5 kg added underneath each roller ski when skating on steep inclines using a different sub-technique ("V1", "Gear 2" or "paddling"). The same research group also reported small but significant changes in muscle coordinative patterns, but no changes in gross efficiency or cycle characteristics when they altered the antero-posterior position of the ski boot according to the rotational hinge.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have noted that differences, such as air drag and surface properties including higher friction on snow, might alter techniques and/or physiological demands, and these should be considered when interpreting experimental findings from roller skiing (Hoffman et al 1994;Kvamme et al 2005;Lindinger et al 2009;Losnegard et al 2012;Sandbakk et al 2012;Andersson et al 2014). However, while the effects of adding weight to the roller skis (Bolger et al 2018) and skiing with different pole lengths (Losnegard et al 2017b(Losnegard et al , 2019Carlsen et al 2018) have been examined, the kinematics of roller skiing and on-snow skiing have, surprisingly, not been compared since the pioneering work in the 1980s (Baumann 1985;Gervais and Wronko 1988).…”
Section: Introductionmentioning
confidence: 99%
“…For example, skiers train nearly half of the year on different types of roller skis which are normally heavier than the skis used in on-snow skiing. The increased ski weight has been proven to affect the metabolic cost and gross efficiency during steep uphill roller skiing in the V1 skating technique [ 13 ]. While skiing on snow, several factors may influence the static and dynamic friction coefficients of the skis, which may further affect the skiing technique.…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains unknown within the group of amateur cross-country skiers and marathon runners-in particular, the impact of the summer preparation period, in which training loads performed in the oxygen zone combined with resistance training dominate. The use of roller skis is also unique, as it not only involves almost all muscles in the body but also relieves the joints [7].…”
Section: Introductionmentioning
confidence: 99%